THE RIGHT TO AUTONOMY: HOW LEGISLATION CAN SUPPORT THE INDEPENDENCE OF CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) (International Seven Journal of Multidisciplinary, 2023)
Autonomy is a fundamental human right that plays a pivotal role in the development of personal independence and empowerment. This is particularly important for children with Autism Spectrum Disorder (ASD), who often experience significant challenges that impede their ability to perform daily activities and make independent decisions. While autonomy is a universally recognized right, children with ASD frequently require specific accommodations and assistive technologies to support their independence in everyday tasks. Assistive tools, such as adaptive footwear, have shown to be vital in improving the mobility, comfort, and overall ability of these children to navigate their environments with greater ease. These tools can address sensory processing issues, motor coordination difficulties, and help children with ASD gain the independence they need to engage more fully in their daily lives. Public policies, educational frameworks, and legal structures are crucial in ensuring that children with ASD have access to the necessary tools and resources that foster their autonomy. Laws like the Americans with Disabilities Act (ADA) and the Individuals with Disabilities Education Act (IDEA) represent significant strides in securing the rights of children with disabilities, but there are still gaps in the implementation of these laws, especially concerning the provision of assistive devices that cater specifically to the needs of children with ASD. This paper explores how public policies, school regulations, and legal rights can support the autonomy of children with ASD by facilitating their access to assistive tools that enhance independence, with a particular focus on adaptive footwear. The article reviews recent academic studies that discuss these issues and highlights the importance of strengthening legislative efforts to ensure that children with ASD receive the support they need to lead independent and fulfilling lives. Additionally, it examines the role of schools and caregivers in providing these necessary accommodations and the need for further training and resources to ensure proper implementation. The findings suggest that a more integrated approach, involving legal, educational, and healthcare systems, is necessary to provide children with ASD the tools they need for greater independence and societal participation.